Furosemide improves the stone clearance rate of extracorporeal shockwave lithotripsy for kidney stones but not ureteral stones: a systematic review and meta-analysis - Feng Yao; Ke Li; ShiQuan Huang; XueSong Cheng; XiaoLiang Jiang (SAGE Journals, 2022)
Introduction:
We conducted a meta-analysis (MA) to investigate the effects of furosemide on the prognosis of extracorporeal shockwave lithotripsy (SWL) therapy to remove renal (RS) and ureteric stones (US).
Methods:
We screened scientific databases including PubMed, Clinicalkey, Google Scholar, Medline, Embase, and Cochrane, from the date of establishment until March 2022, to search for randomized controlled trials evaluating SWL, in combination with furosemide (experimental group) or with SWL alone (control group), in treating RS or US. Our search terms included furosemide, extracorporeal SWL, and urolithiasis. For this MA, we employed the Cochrane Collaboration’s RevMan version 5.3.0.
Results:
Six trials, involving 1344 participants, with RS (n = 1097) and/or US (n = 247), met our predefined criteria. This included 137 proximal ureteral stones (PUSs), 35 mid-ureteral stones (MUS), and 75 distal ureteral stones (DUS). In case of RS, the experimental group exhibited significantly enhanced clearance, relative to controls (risk ratio [RR] = 1.16, 95% confidence interval [CI] = 1.07–1.25, p = 0.0002), yet there was no obvious difference in the PUS, MUS, and DUS (RR = 1.14, 95% CI = 0.97–1.33, p = 0.10; odds ratio [OR] = 1.26, 95% CI = 1.40–3.95, p = 0.69; RR = 1.21, 95% CI = 0.99–1.49, p = 0.06). There was also no marked difference between fragmentations in either group. Only reports of SWL treatment of RS provided adequate data on shocks, sessions, and complications for our analysis. Unfortunately, there was no significant alteration between the two groups.
Conclusion:
According to our analysis, furosemide strongly accelerates the clearance rate of SWL-treated RS. However, it does not enhance the fragmentation rate. Given this evidence, we propose that furosemide does not significantly improve the efficacy of SWL therapy in removing US.
Registration:
Our work is registered with PROSPERO (CRD42020204780).
Keywords: Paediatrics; Pharmacology and Pharmaceutical Sciences not elsewhere classified